PENGARUH KUALITAS PELAYANAN, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PELANGGAN MENGGUNAKAN JASA PENGENDALIAN HAMA (FUMIGASI) PADA PT SUCOFINDO (PERSERO) KANTOR CABANG SEMARANG - Pretty Caroline Adiningrum; Suryadi - Poerbo; Rusmini - Rusmini (Politeknik Negeri Semarang, 2015)
Exports in Indonesia progress quite rapidly.This can be seen by many exporters competeto market their products abroad. Exporterscompeting to provide and give the best fortheir customers. Therefore, it is neededactivities to protect the goods from pestsattacks with fumigation. Nowadays a lot offumigator are trying to offer the bestfumigation services for exporters.This study aims to identify and analyze theinfluence of service quality, price andpromotion to the customer's decision to usethe services of fumigation in PT SucofindoSemarang.Sampling using total sampling technique.With a target of 90 customers which use theservices of fumigation in PT SucofindoSemarang. Data collecting method usedquestionnaires, interviews and observation.Data were measured using a linear scale.Data processing with hypothesis testing usinglinear regression analysis.The result shows that there are 7 independentvariables affect the customer's decision to usethe services of fumigation campaign in whichpromotion variables are independentvariables that have the highest influencevalue. And the price variable is theindependent variable that has the smallestinfluence on customer decision variables touse the services of fumigation in PT SucofindoSemarang. Rated R sequare = 71.3% meansthat the variable relationship is quite tight.